Synthesis of highly dispersed phosphotungstic acid encapsulated in MIL-100(Fe) catalyst and its performance in heterogeneous oxidative desulfurization. Issue 12 (2nd December 2019) - Zhang, Dongxu; Song, Hua; Yuan, Dandan
Abstract: Highly efficient HPW( x )/MIL-100(Fe) catalysts with different phosphotungstic acid (HPW) loading ( x, wt%) were successfully synthesized by a one-step hydrothermal method and characterized by XRD, SEM, FTIR, and BET. The influences of HPW loading, catalyst dosage, temperature, and O/S molar ratio on oxidative desulfurization (ODS) were investigated. The results indicated that the HPW( x )/MIL-100(Fe) retained the structure of its parent MIL-100(Fe). The MIL-100(Fe) presented a high surface area, which is beneficial to dispersion of HPW. The HPW( x )/MIL-100(Fe) with HPW loading of 40% exhibited excellent ODS activity. At a temperature of 50 °C, a catalyst dosage of 0.06 g, and an O/S molar ratio of 4, 100% desulfurization was achieved within 90 min for benzothiophene, dibenzothiophene, and 4, 6-dimethyl-dibenzothiophene. The high catalytic activity of HPW( x )/MIL-100(Fe) can be attributed to highly dispersed HPW active sites with a high specific surface area.